Future Socio-Political Scenarios for Aquatic Resources in Europe: A Common Framework Based on Shared-Socioeconomic-Pathways (SSPs) - Pinnegar, John K.; Hamon, Katell G.; Kreiss, Cornelia M.; Tabeau, Andrzej; Rybicki, Sandra; Papathanasopoulou, Eleni; Engelhard, Georg H.; Eddy, Tyler D.; Peck, Myron A. (Frontiers in Marine Science, 2021)
It has proven extremely challenging for researchers to predict with confidence how human societies might develop in the future, yet managers and industries need to make projections in order to test adaptation and mitigation strategies designed to build resilience to long-term shocks. This paper introduces exploratory scenarios with a particular focus on European aquaculture and fisheries and describes how these scenarios were designed. Short-, medium- and long-term developments in socio-political drivers may be just as important in determining profits, revenues and prospects in the aquaculture and fisheries industries as physical drivers such as long-term climate change. Four socio-political-economic futures were developed, based partly on the IPCC SRES (Special Report on Emissions Scenarios) framework and partly on the newer system of Shared Socio-economic Pathways (SSPs). ‘Off the shelf’ narrative material as well as quantitative outputs were ‘borrowed’ from earlier frameworks but supplemented with material generated through in-depth stakeholder workshops involving industry and policy makers. Workshop participants were tasked to outline how they thought their sector might look under the four future worlds and, in particular, to make use of the PESTEL conceptual framework (Political, Economic, Social, Technological, Environmental, and Legal) as an aide memoire to help define the scope of each scenario. This work was carried out under the auspices of the EU Horizon 2020 project CERES (Climate change and European aquatic RESources), and for each ‘CERES scenario’ (World Markets, National Enterprise, Global Sustainability and Local Stewardship), additional quantitative outputs were generated, including projections of future fuel and fish prices, using the MAGNET (Modular Applied GeNeral Equilibrium Tool) modeling framework. In developing and applying the CERES scenarios, we have demonstrated that the basic architecture is sufficiently flexible to be used at a wide diversity of scales. We urge the climate science community to adopt a similar scenarios framework, based around SSPs, to facilitate global cross-comparison of fisheries and aquaculture model outputs more broadly and to harmonize communication regarding potential future bioeconomic impacts of climate change.